Coupling of surface air and sea surface temperatures in the CERA‐20C reanalysis. (3rd January 2018) - Feng, Xiangbo; Haines, Keith; de Boisséson, Eric
Abstract : ECMWF has recently produced its first ocean‐atmosphere coupled twentieth century reanalysis CERA‐20C, with ten ensemble members. CERA‐20C is based on a coupled climate model with data assimilation implemented individually for the atmosphere and ocean components. This article focuses on the relationships between 2 m air temperature (T2m) and sea surface temperature (SST) in this new coupled climate reanalysis from the perspective of ensemble statistics. The results show where the atmosphere or the ocean are driving the ensemble variability of temperature at the air–sea interface on varying time‐scales. In CERA‐20C, the T2m–SST ensemble relationships are changing on diurnal, seasonal and longer time‐scales and also within regions. The T2m ensemble spread is much larger than the SST ensemble spread at high frequencies (3 h), normally with low correlations due to different time‐scales of oceanic and atmospheric dynamics, showing the atmospherically driven variability of T2m. On monthly time‐scales, the T2m spread is mostly slightly lower than the SST spread, with high correlations and strong coupling, reflecting the SST‐forced variability. T2m–SST coupling is strongest where atmospheric and oceanic boundary layers are shallow, e.g. in the summer hemisphere, and weakest where the atmospheric boundary layer becomes deep, e.g. in the ITCZ region. As the twentieth century progresses, ensemble spreads decline, while T2m–SST coupling becomes stronger as both atmosphere and oceans are better constrained to observations. In the Tropics, strong ENSO‐related variability is found in T2m–SST coupling as atmospheric convection centres move interannually to break the SST‐dominated relationships. Abstract : Air–sea coupling in the new coupled reanalysis CERA‐20C is examined by focusing on the ensemble variability of temperature at the interface. Surface air temperature is less constrained by SST at high‐frequency time‐scales, but is more forced by SST at long time‐scales. Air–sea coupling is strongest where atmospheric and oceanic boundary layers are shallow, and weakest where the atmospheric boundary layer becomes deep. As more observations become available through the twentieth century, air–sea coupling increases, except in the Tropics.